Kinematic and kinetic analysis of taekwondo poomsae side kick according to various heights of the target - Hong, A. R.; So, J. M. (Korean Journal of Sport Biomechanics, 2019)
Objective: The purpose of this study is to present the scientific and quantitative data by finding the common points and differences of the side-kick according to the height change through the difference of the side kick motion performance according to the three target height changes and the function of the lower limbs muscle in side kick motion of Taekwondo Poomsae. Method: For this, total 14 players were selected who were registered in Korea Taekwondo Association and skilled group 7 players who had a medal from national competition and 7 players who did not have Taekwondo experience from department of physics. 4 video cameras to the feature on side kick per target height, and the subjects' support foot was located on the ground reactor and the practice was conducted 3 times: waist, chest, and head as the target height. the basic materials were collected by using Kwon 3D XP program and the T-test was conducted to verify the statistic difference between groups (SPSS 24.0). At this time, the statistics significance level was set as .05 and the following conclusion was obtained. Results: The lower the proficiency and the higher the height, the more the joint coordination between the hip and the knee. Conclusion: Summary of the result shows a common point that the change of target's height makes the lower the proficiency and the higher the height, the more the joint coordination between the hip and the knee. Also, the higher the target's height became, the greater angular momentum of thighs, shanks, foot became in common.